Dynamics of two distinct memory interactions during water seeking in Drosophila - Lee, Wang-Pao; Chiang, Meng-Hsuan; Chao, Yi-Ping; Wang, Ying-Fong; Chen, Yan-Lin; Lin, Yu-Chun; Jenq, Shan-Yun; Lu, Jun-Wei; Fu, Tsai-Feng; Liang, Jia-Yu; Yang, Kai-Cing; Chang, Li-Yun; et al. (Proceedings of the National Academy of Sciences - PNAS, 2025)
Forming and forgetting memories shape our self-awareness and help us face future challenges. Therefore, understanding how memories are formed and how different memories interact in the brain is important. Previous studies have shown that thirsty flies sense humidity through ionotropic receptors, which help them locate water sources. Here, we showed that thirsty flies can be trained to associate specific odors with humidity to form a humidity memory that lasts for 30 min after association. Humidity memory formation requires the Ir93a and Ir40a ionotropic receptors, which are essential for environmental humidity sensing. Water memory takes precedence, leading to the forgetting of humidity memory by activating a small subset of dopaminergic neurons called protocerebral anterior medial (PAM)-γ4, that project to the restricted region of the mushroom body (MB) γ lobes. Adult-stage-specific silencing of Dop2R dopaminergic receptors in MB γ neurons prolongs humidity memory for 3 h. Live-brain calcium imaging and dopamine sensor studies revealed significantly increased PAM-γ4 neural activity after odor/humidity association, suggesting its role in forgetting the humidity memory. Our results suggest that overlapping neural circuits are responsible for the acquisition of water memory and forgetting humidity memory in thirsty flies.